Majida Ghazi . M . AL- Jorani Effect of Hyperprolactinaemia on concentration of immunoglobulins and complement components in a series of infertile Iraqi women - Ghazi, Majida (University of Thi-Qar Journal of Science, 2019)
The present study was designed to detection the imunoglobulins concentration and complement compenent effects by hyperprolactinaemia The sample included patients, who were attending the Institute for Embryo Research and Infertility Treatment for diagnosis and treatment In Bagdad city during the period 200 -April -to -200 -Septemper . primary infertile females patients with hyperprolactinaemia (age range: 20 – 40 years) were investigated.The collected serum was tested for the determination of prolactin levels using a miniVidas system. (serum level of prolactin ≥ ng/ml), the total patients were divided into three groups; I ( patients), II ( patients) and III ( patients), Their serum prolacin levels were 22-29, 30-39 and ≥ 40 ng/ml, respectively. ( single radial immunodiffusion test) , used to Quantitative Measurement of Immunoglobulins(IgA, IgG and IgM) and Complement components C3 and C4 which was developed by( Mancini et al. 1965). The immunoglobulins (IgA, IgG and IgM) showed a significant increased total level in the sera of total patients when compared with controls, (265.5 vs. 225.3, 1423 vs. 1076 and 266 vs. 188 mg/dl, respectively With respect to complement components, the serum levels of C3 and C4 were slightly decreased in the patients, but the difference did not reach a statistical level .